2017
DOI: 10.3389/fpsyt.2017.00173
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Comorbid Alcohol Dependence and Anxiety Disorder: Review of the Scientific Evidence and Recommendations for Treatment

Abstract: Patients with alcohol-use disorders (AUDs) have a high prevalence of anxiety disorders (AnxDs). “Co-occurring disorders” refers to the coexistence of an AUD and/or drug related disorders with another non-addictive psychiatric disorder. The aim of this study was to assess the effectiveness of psychopharmacological treatments and psychotherapy in patients with AUD and AnxD and to propose recommendations for the treatment of patients with comorbid AnxDs and AUDs. Randomized clinical trials, meta-analyses, and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 91 publications
0
30
0
2
Order By: Relevance
“…In particular, alcohol consumption is strongly associated with suicides, and this may be due to low serotonin activity leading to aggressiveness and impulsivity . In addition, alcohol dependence often coexists with depression and anxiety disorders , with alcohol use often being a form of self‐medication to manage depression and anxiety , and this psychiatric comorbidity has a major impact on suicidal behaviour . Alternatively, having a religion may lead to empowerment, sense of meaning in life or positive affects, and these may buffer individuals from suicidal behaviour .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, alcohol consumption is strongly associated with suicides, and this may be due to low serotonin activity leading to aggressiveness and impulsivity . In addition, alcohol dependence often coexists with depression and anxiety disorders , with alcohol use often being a form of self‐medication to manage depression and anxiety , and this psychiatric comorbidity has a major impact on suicidal behaviour . Alternatively, having a religion may lead to empowerment, sense of meaning in life or positive affects, and these may buffer individuals from suicidal behaviour .…”
Section: Discussionmentioning
confidence: 99%
“…High comorbidity rates exist between SUD and AD. [35][36][37] Studies had shown that high AD is related to increased use of substances, increased severity of alcohol withdrawal, and higher relapse rates following substance abuse treatment, 15,[38][39][40] as well as HADDAD ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, studies have reported clinical cases where treatment with SSRIs appears to be the cause of increased frequency of intoxication by alcohol and new onset of alcohol-related problems [103][104][105]. Finally, patients who actively drink suffering of comorbid anxiety and AUD have also shown that they may increase alcohol consumption under treatment with SSRIs [106].…”
Section: Clinical Evidence Of Antidepressant Treatment Improves Deprementioning
confidence: 99%